Managed software evolution - Reussner, Ralf; Goedicke, Michael; Hasselbring, Wilhelm; Vogel-Heuser, Birgit; Keim, Jan; Märtin, Lukas (Springer, 2019)
1 Introducing Managed Software Evolution -- 2 The Nature of Software Evolution -- 3 Addressed Challenges -- 4 Introduction to Case Studies -- 5 Tacit Knowledge in Software Evolution -- 6 Continuous Design Decision Support -- 7 Model-based Round-Trip Engineering and Testing of Evolving Software Product Lines -- 8 Performance Analysis Strategies for Software Variants and Versions -- 9 Maintaining Security in Software Evolution -- 10 Learning from Evolution for Evolution -- 11 Formal Verication of Evolutionary Changes -- 12 Case Studies for the Community -- 13 Lessons Learned -- 14 Future Research